PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PERPAJAKAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Agni, Mayka Nur; -, Masripah (Jurnal Ilmiah Raflesia Akuntansi, 2023)
The purpose of this research is to find out whether there is influence from taxpayer awareness, tax socialization, and tax sanctions on the mandatory compliance of MSMEs in the culinary sector in Jakarta. Quantitative method as the primary data source as the type of data in this study with the sample being taxpayers of MSME culinary sector who are registered with the Office of Industry, Trade, Cooperatives, Small and Medium Enterprises in the Jakarta area. The use of purposive sampling as a data collection technique with a sample of 100 respondents. Data testing was carried out using the Partial Least Square method with the help of SmartPLS 3.0 software. The results of this study indicate that taxpayer awareness, tax socialization, and tax sanctions have a positive and significant effect on MSME taxpayer compliance in the culinary sector in Jakarta.